CARDIAC ARRHYTHMIAS IN MEDICAL PRACTICE: CLINICAL CASE OF AMIODARONE-INDUCED THYROTOXICOSIS TYPE 2 AS A CAUSE OF RECURRENT ATRIAL FIBRILLATION - O. V. Gaisenok (Столичная издательская компания, 2016)
Atrial fibrillation is a common cardiac arrhythmia. Amiodarone is an effective drug used for atrial fibrillation treatment. Various side effects of this drug including amiodarone-induced thyrotoxicosis are discussed. A clinical case is presented to provide data for the differential diagnosis between types 1 and 2 of amiodarone-induced thyrotoxicosis and to define approaches to the treatment.